The Impact of COVID-19 Public Health Measures on Detection of Other Respiratory Viruses in Children during the Winter of 2020–2021 in Hangzhou, China - Xiang, Wen-qing; Li, Lin; Guo, Ya-jun; Lin, Jian; Li, Wei (Journal of Pediatric Infectious Diseases, 2022)
Objective Acute respiratory tract infection (ARTI) is one of the main diseases in childhood. This study aimed to monitor the distribution of respiratory tract viruses in children with ARTI in the impact of coronavirus disease 2019 (COVID-19).Methods We conducted surveillance of 2019 novel coronavirus, human metapneumovirus, respiratory syncytial virus, human adenovirus, human parainfluenza virus 1–3, and influenza A and B virus by using quantitative real-time polymerase chain reaction.Results During the winter of 2020 to 2021, among the 1,442 throat swabs we collected, 937 (64.98%, 937/1,442) were positive for respiratory viruses. Respiratory syncytial virus was the most frequently detected respiratory virus (34.12%, 492/1,442) and 2019 novel coronavirus and influenza A and B virus were not detected in the study period. Coinfection was observed in 156 positive samples including 149 samples of double infection and 7 of triple infection. The positive rate of viral respiratory tract infection in infants less than 6 months was the highest (72.95%) in the study period.Conclusion There are some differences in the distribution of respiratory viruses in children after the outbreak of COVID-19 in Hangzhou, China.
Keywords: acute respiratory infection; virus; children; COVID-19